Kinematics, Kinetics, and Electromyography of Vertical and Horizontal Hip Extension Exercises and Their Transference to Acceleration and Power - Contreras, Bret (Auckland University of Technology, 2015)
The squat is a very popular exercise in resistance training, utilized by populations ranging from clinical to elite athletes. A myriad of literature has shown that squats are effective for improving strength, performance, and hypertrophy. Due to the inherent nature of the squat, it is loaded vertically, or axially. The hip thrust, however, is a new, horizontally-, or anteroposteriorly-loaded exercise utilized to work the hip extensors, especially at end-range hip extension. The nature of the hip thrust makes it especially useful for achieving maximal gluteus maximus activation, as maximal activation is elicited at end-range hip extension, and may therefore be useful for achieving remarkable increases in gluteus maximus strength and hypertrophy. Furthermore, the horizontal nature of the hip thrust may mean that it carries over well to horizontally-oriented activities, such as pushing or sprinting. In order to test these hypotheses, a number of studies were carried out. Interestingly, it was found that there is no statistically significant difference in electromyographic amplitude between squat parallel, full, and front squat variations, and that there is no difference (p > 0.05) in electromyographic amplitude between barbell, American, and band hip thrust variations. The barbell hip thrust elicits much greater (mean upper gluteus maximus ES = 1.55; mean lower gluteus maximus ES = 1.65; mean biceps femoris ES = 1.58) hip extensor electromyographic activity than does the parallel squat, and is also beneficial for concentric force outputs (ES = 0.48). The squat, however, displayed a number of kinetic and temporospatial advantages over the hip thrust, including greater bar displacement (ES = 5.59) and potentially total work, impulse, and repetition time (ES = 0.51–1.00). A randomized-controlled trial was then performed to investigate how these differences transfer to training in adolescent male athletes. It appears that the hip thrust effectively improves a number of performance measures, including 20 m sprint times (ES = 1.14) and isometric mid-thigh pull strength (ES = 1.11). The front squat effectively increased vertical jump (ES = 1.11). Between-group comparisons revealed a number of benefits to the hip thrust over the front squat, including 10 and 20 m sprint times (ES = 0.32 and 0.39, respectively) and isometric mid-thigh pull strength (ES = 1.35 and 0.76 for absolute and normalized, respectively), and possible trivial benefits for horizontal jump performance (ES = 0.15). The front squat displayed a possibly beneficial effect for vertical jump performance (ES = –0.47). Finally, a single-subject six-week training study was conducted on monozygotic twins, wherein gluteus maximus hypertrophy and strength outcomes were measured. The squat and hip thrust exercises both increased upper and lower gluteus maximus thickness (upper: 20.7% (squat) vs. 23.5% (hip thrust); lower: 20.3% (squat) vs. 23.1% (hip thrust)), with the hip thrust being more effective at increasing upper gluteus maximus thickness compared to the squat (upper: 2.73%; lower: 2.89%). The hip thrust increased maximum horizontal force, 1 RM hip thrust, and 1 RM squat strength (31.8–65.0%), whereas the squat only increased 1 RM squat and 1 RM hip thrust (19.9–63.2%). This thesis provides evidence that the direction of the force vector in relation to the exerciser’s body plays a role in determining the transfer to performance.
Keywords: Hip extension; Force vector; Gluteus maximus; Hip thrust; Squat; Horizontal force